Pengaruh Likuiditas, Pertumbuhan Perusahaan, Ukuran Perusahaan, Leverage, Dan Kekuatan Pasar Terhadap Kinerja Perusahaan - Lintang Sekar (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2024)
The focus of this research is to examine the impact of liquidity, company growth, company size, leverage and market power on the performance of the manufacturing industry as recorded on the Indonesia Stock Exchange (BEI) in 2020 - 2022. This research is based on 5 independent variables with 5 types of measurements. empirically tested for its correlation with company performance. These variables are liquidity (current ratio), company growth (estimated by sales growth), company size (total sales), leverage (Debt Equity Ratio), and market power (Lerner index). Secondary data used in this research was obtained via the website www.idx.co.id. The purposive sampling method is used as a sampling method by selecting a population sample based on the criteria of the researcher's wishes. Multiple regression analysis is used as a research method to understand the correlation between more than two variables. The results of data processing show that liquidity has a partial positive impact on company performance as measured by ROA. Meanwhile, the variables company growth, company size, leverage and market power have no impact on company performance as measured by ROA.